Utilizando jogos eletrônicos para o ensino das leis de Newton no primeiro ano do ensino médio - Lima, Allan Lopes (2021)
Teaching physics in our country presents great challenges, as teaching methods have not evolved along with the technology we have available. Physics teaching is based on traditional methods, which for a large part of students are not attractive, because outside the classroom they are used to using technology for the most different tasks. The present work seeks to present a method inspired by the ideas of the Behaviorist Skinner thinker, allied to the principles of Vygotsky's socio-affective interaction, as well as the concepts of significant learning by Ausubel, to insert the use of cell phones and electronic games in the teaching-learning process. With this vision in mind, a mobile game was developed, addressing issues related to the concepts and applications of Newton's laws. This work was applied at the state school Marcantônio Vilaça II, known as CMPM II, in the city of Manaus, Amazonas. The application of the project consisted of evaluating two classes, to compare yields. In one class, the game was used as part of the teaching-learning process, in the other class the activities were worked out using the traditional expository method and with exercise resolutions. The two classes initially had expository classes, presentation of concepts, but when working on activities, in one it was solving exercises and in the other the activity was for the student to be entertained with the game. At the end of the didactic sequence, a test was applied to assess which of the classes managed to better absorb the content. The useof games was well accepted by students, and at the end of this work we will show how this contributed to meaningful learning.